Posture, flexibility and grip strength in horse riders - Hobbs, S. J.; Baxter, J.; Broom3, L.; Rossell, L.-A.; Sinclair, J.; Clayton, H. M. (Journal of Human Kinetics, 2014)
Since the ability to train the horse to be ambidextrous is considered highly desirable, rider asymmetry is recognized as a negative trait. Acquired postural and functional asymmetry can originate from numerous anatomical regions, so it is difficult to suggest if any is developed due to riding. The aim of this study was therefore to assess symmetry of posture, strength and flexibility in a large population of riders and to determine whether typical traits exist due to riding. 127 right handed riders from the UK and USA were categorized according to years riding (in 20 year increments) and their competition level (using affiliated test levels). Leg length, grip strength and spinal posture were measured and recorded by a physiotherapist. Standing and sitting posture and trunk flexibility were measured with 3-D motion capture technology. Right-left differences were explored in relation to years riding and rider competitive experience. Significant anatomical asymmetry was found for the difference in standing acromion process height for a competition level (-0.07±1.50 cm Intro/Prelim; 0.02±1.31 cm Novice; 0.43±1.27 cm Elementary+; p=0.048) and for sitting iliac crest height for years riding (-0.23±1.36 cm Intro/Prelim; 0.01±1.50 cm Novice; 0.86±0.41 cm Elementary+; p=0.021). For functional asymmetry, a significant interaction was found for lateral bending ROM for years riding x competition level (p=0.047). The demands on dressage riders competing at higher levels may predispose these riders to a higher risk of developing asymmetry and potentially chronic back pain rather than improving their symmetry.